2021
DOI: 10.3389/fnut.2021.740855
|View full text |Cite
|
Sign up to set email alerts
|

Association of Serum 25-Hydroxyvitamin D Concentrations With All-Cause and Cause-Specific Mortality Among Adult Patients With Existing Cardiovascular Disease

Abstract: Background: Vitamin D insufficiency and deficiency are common in patients with cardiovascular disease (CVD). We aimed to prospectively examine the associations of serum 25-hydroxyvitamin D [25(OH)D] concentrations with all-cause and cause-specific mortality among adult patients with existing CVD.Methods: We included 37,079 patients with CVD from the UK Biobank study, a prospective cohort of half a million participants aged 40–69 years. We defined patients with CVD as those who suffered coronary heart disease, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 47 publications
(75 reference statements)
0
20
0
Order By: Relevance
“…Similarly, a study based on UK Biobank participants who had CVD followed for a median of 11.7 years showed a linear inverse association of CVD mortality ( P -non-linearity = 0.07) with 25(OH)D, the adjusted HR decreasing from 1.31 (95% CI, 1.14 to 1.43) at 4 ng/mL to 0.83 (95% CI, 0.77 to 0.88) at 15 ng/mL and then (linearly) to 0.37 (95% CI, 0.22 to 0.62) at 60 ng/mL [ 9 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, a study based on UK Biobank participants who had CVD followed for a median of 11.7 years showed a linear inverse association of CVD mortality ( P -non-linearity = 0.07) with 25(OH)D, the adjusted HR decreasing from 1.31 (95% CI, 1.14 to 1.43) at 4 ng/mL to 0.83 (95% CI, 0.77 to 0.88) at 15 ng/mL and then (linearly) to 0.37 (95% CI, 0.22 to 0.62) at 60 ng/mL [ 9 ].…”
Section: Resultsmentioning
confidence: 99%
“…All-cause mortality rate Observational study of 25(OH)D concentration due to vitamin D supplementation >30 ng/mL [8] Alzheimer's disease and dementia Meta-analysis of observational studies >25 ng/ml [93] Breast cancer Observational study of 25(OH)D concentration due to vitamin D supplementation >60 ng/mL [33] Colorectal cancer Meta-analysis of observational studies 30-40 ng/mL [34] Cardiovascular disease Observational study of the CVD mortality rate for CVD patients >30 ng/mL [9] Myocardial infarction Observational study of 25(OH)D concentration due to vitamin D supplementation'1n >30 ng/mL [8] SARS-CoV-2 infection Retrospective observational study >50 ng/mL [75] COVID-19 mortality Retrospective cohort study >60 ng/mL [82] Diabetes mellitus type 2 RCT with an analysis of intratrial 25(OH)D for prediabetes patients >50 ng/mL [70] Gene expression Clinical trial >40 ng/mL [45] Hypertension Observational study of 25(OH)D concentration due to vitamin D supplementation >40 ng/mL [16] Preterm delivery Observational study of 25(OH)D concentration due to vitamin D supplementation >40 ng/mL [106] It has been shown experimentally that humans can produce between 10,000 and 25,000 IU of vitamin D through whole-body exposure to one minimal erythemal dose of simulated sunlight, i.e., one instance of mid-day sun exposure without burning [107]. Thus, doses to those levels should be considered inherently safe.…”
Section: Outcome Type Of Evidence Optimal 25ohd Referencementioning
confidence: 99%
“…Studies have shown that daily vitamin D supplementation to maintain serum 25(OH)D levels ≥100 nmol/L is a promising approach to reduce the risk of diabetes in adults with prediabetes ( 26 ). Studies have shown that in CVD patients, elevated serum 25(OH)D levels are associated with a reduced risk of all-cause and cause-specific mortality ( 27 ). Studies have shown that in patients with vitamin D deficiency and no history of myocardial infarction, maintaining (25-OH)D levels at 30 ng/mL at the time of treatment is associated with a lower risk of myocardial infarction ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, vitamin D deficiency has been reported to be common in patients with cardiovascular disease (CVD) [ 90 , 91 ]. The Mendelian randomization analyses performed in four population-based cohort studies found an inverse association between the results of coronary heart disease, stroke, and all-cause mortality with a low serum concentration of this vitamin [ 92 ].…”
Section: Dietary Recommendations For Patients With Post-covid-19 Synd...mentioning
confidence: 99%